(untitled) (Bangladesh Journal of Urology, 2020)
Objective: To observe the improvement of the symptoms of pelvic pain, dysuria and haemospermia after treatment with magnetic infrared laser therapy in patients with chronic pelvic pain syndrome. Methods : This study was an observational study done on 30 male patients with pelvic pain and age range varied from 30 to 60 years. The study was conducted from 2009 to 2011 in a private medical center in Dhaka city . The MIL-therapy in use has a wave length of 904 nm and a frequency of 3000 Hz. The Laser beam reaches the prostate with a special optic probe. In this study the patients were examined per rectally by doing digital rectal examination with use of gloves and gel. At the beginning we used a “Laser Super Sonic” machine with endorectal probe according to Strada. The treatment schedule was one treatment every two days (treatment’s time of 5/10 minutes, wave length 1000 KHz)) for a total of 10 applications. After 10 applications patients were asked for follow-up and data were callected and analysed. Results : Out of 30 patients of chronic pelvic pain syndrome aged between 30-60 yrs with compains of pelvic pain, dysuria and haemospermia were under treatment with MIL therapy. 18 patients with pelvic pain, 13 patients with dysuria and 04 patients with haemospermia were cured after laser treatment . There were improvement of symptoms of pelvic pain in 11 patients, dysuria in 07 patients after laser therapy . But 01 patient found not improved . Among 30 cases 23 patients found normal sized prostate and 07 found enlarged prostate on digital rectal examination and on USG findings, 21 were found normal sized, 09 found enlarged sized prostate and 07 patients had increased PVR Conclusion : Patient sign and symptoms improved significantly after M/L therapy. Bangladesh Journal of Urology, Vol. 17, No. 1, Jan 2014 p.42-46